The development of electric 2 and 3-Wheelers for low carbon passenger transport: A long-term benefits assessment - Campisi, Tiziana; Ali, Nazam; Akgün, Nurten; Canale, Antonino; Tesoriere, Giovanni (American Institute of Physics Inc., 2022)
Shared mobility can play an important role in many of the nations by reducing negative impacts of traffic. The emergency of the shared mobility concept makes it possible to achieve the Sustainable Development Goals by meeting with the decarbonization strategies such as Green Deal and 2030 Agenda. In the near future, it is expected that shared mobility and innovative transport systems will reshape urban mobility by reducing negative impacts on environment and promoting smart and sustainable travel options. More in particular, electric based shared mobility modes could represent the future with being more environment-friendly and energy-efficient. Among different types of shared means of transport, rickshaws have been becoming popular in South-East Asia, which initially involved as human traction, large size, and traditional pedicab tricycles but have evolved into electrified vehicles. Low-cost Chinese models were the first electric rickshaws which become popular. Currently, electric rickshaws are commonly used in many of the countries in Asia, particularly in China, India, Bangladesh, and Nepal. Some European countries, such as Switzerland, France and Germany, have researched and developed shared electric bike (e-bike) and electric bike taxi (ebike-taxi) services and have been trying to capture the growing market in Asia. The governments in European countries are making serious efforts to improve the number of these mode of transport by making policies such as issuing license with reduced fee. In this paper, the uptake of using shared e-bikes, ebike-taxis and electric rickshaws is presented. The benefits of using these modes in urban areas and the critical issues related to the diffusion are also discussed. This study lays foundation for the improvement of different urban planning and mobility strategies in Sustainable Urban Mobility Plans by providing critical suggestions, which are fundamental for the development of best practices as a guiding tool for local authorities and mobility service providers. © 2022 Author(s).
International Conference of Computational Methods in Sciences and Engineering 2021, ICCMSE 2021 -- 2021-09-04 through 2021-09-07 -- Heraklion -- 184643
Keywords: Decarbonisation strategies; Electric rickshaws; Shared mobility; SUMP